2003
DOI: 10.1105/tpc.009308
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-Wide Analysis of NBS-LRR–Encoding Genes in Arabidopsis[W]

Abstract: The Arabidopsis genome contains ‫ف‬ 200 genes that encode proteins with similarity to the nucleotide binding site and other domains characteristic of plant resistance proteins. Through a reiterative process of sequence analysis and reannotation, we identified 149 NBS-LRR-encoding genes in the Arabidopsis (ecotype Columbia) genomic sequence. Fifty-six of these genes were corrected from earlier annotations. At least 12 are predicted to be pseudogenes. As described previously, two distinct groups of sequences wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

106
1,765
5
7

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,464 publications
(1,883 citation statements)
references
References 126 publications
106
1,765
5
7
Order By: Relevance
“…Genomic organization of the Rpi-blb1 gene cluster Many R genes are present within clusters of tightly linked genes (Michelmore and Meyers 1998;Meyers et al 2003). This is also the case for the Rpi-blb1 gene (van der Vossen et al 2003).…”
Section: Discussionmentioning
confidence: 90%
“…Genomic organization of the Rpi-blb1 gene cluster Many R genes are present within clusters of tightly linked genes (Michelmore and Meyers 1998;Meyers et al 2003). This is also the case for the Rpi-blb1 gene (van der Vossen et al 2003).…”
Section: Discussionmentioning
confidence: 90%
“…Our results indicate that, although many R gene clusters are indeed conserved between potato and tomato, many may be part of heterogeneous superclusters which harbor more than a single RGA family. For Arabidopsis, it was reported that »10% of the NBS-LRR clusters contained NBS-LRR genes of diverse subgroups but that these clusters are likely the result of random associations among the 149 NBS-LRR-encoding genes in the Arabidopsis Col-0 genome (Meyers et al 2003). For tomato Pan et al (2000) also found genetic linkage between NBS containing R gene sequences from diVerent origin.…”
Section: Discussionmentioning
confidence: 99%
“…3) shows that most contained a 'VGIWG' aa motif upstream of the NBS primer. This is found as the P-loop motif in some Toll-interleukin-1 receptor/NBS/LRRtype RGAs such as those in Arabidopsis thaliana (Meyers et al 2003). This means that the two degenerate primers used were actually anchored in the specific P-loop motif of the disease resistance proteins.…”
Section: Most Of the Nbs Markers Are Rgasmentioning
confidence: 99%
“…Speulman et al 1998;Geffroy et al 2000;Gebhardt and Valkonen 2001), and thus may provide either interesting candidate genes or useful markers for marker-assisted selection (MAS). They also provide information about the organization and evolution of resistance genes and RGAs in plant genomes (Grube et al 2000;Pan et al 2000;Bai et al 2003;Meyers et al 2003).…”
Section: Introductionmentioning
confidence: 99%